Фольклористичність викладу у творах Марка Вовчка - Ляшишина, Валерія Віталіївна; Liashyshyna, Valeriia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано наративну стратегію окремих творів малої прози Марії Вілінської. Досліджено, що письменниця в оповіданнях привертає до себе увагу читача правдивою присутністю, лаконічністю розповіді та поглядами на життя. Саме завдяки цьому Марко Вовчок змогла досягти однієї з головних особливостей своїх творів – фольклористичності викладу.The article analyzes the narrative strategy in some small works of prose Mariia Vilinska in particular focus on the presence of the narrator in the works, its reality and truth of the stories he tells. In many works of Marko Vovchok story is told in the first person, which is an ordinary man, often a woman of the people. Language works of the writer is very simple and concise. It is the direct participants in the events who talk about different cases of life of those to which they had heard of them, or they just watched. These storytellers play an important role, because it is transmitted through the entire flavor of that time of life, traditions and more. In addition, they perform several functions, one of which is depicted the creation of impressions maximum authentication. That is, it is not just a folk story, but also a kind of retelling of the folk (folk form of presentation). In her writings Marko Vovchok merges with the people, counterfeited under her tongue, becoming part of its folklore, which is characteristic of her work.
Folklore of Presentation in Marko Vovchok Works Brand
Keywords: наратор; фольклористичність; оповідь; мала проза; Марко Вовчок; narrator; folklore; narrative; small works of prose; Marko Vovchok